Histological, Histochemical and Gene Expression Analysis of Mucin 1,4 in the Small Intestine of Owl (Tyto Alba) - Abass, Russul; Hacham, Iman Ibrahim Al (American Journal of Biodiversity, 2025)
The point of this study is to look at how environmental and dietary factors affect the small intestines of owls by looking at the histological features and gene expression of mucin proteins. We compared the histochemical and gene expression profiles of MUC1 and MUC4 proteins present in the small intestines of owls. The small intestine of the owl was characterised by a layer of simple, columnar epithelium interspersed with goblet cells. The duodenum organizes the muscular mucosa into a single set of longitudinal fibres, while the submucosa constitutes a substantial layer of loose connective tissue. The jejunum exhibited a mucous membrane characterised by numerous large villi, while the ileum had simple columns and goblet cells. The RT-PCR amplification plots of the MUC1 and MUC4 genes in the owl's duodenum, jejunum, and ileum showed different Ct cycle numbers, which were between 20 and 25. The melting peaks for the MUC1 of owl were in the ranges of 65-85°C, while the melting peaks for the housekeeping gene, MUC4, owl were in the ranges of 65-80°C. The results of this study give us a lot of information about the structure, expression, of MUCs in owls. This helps us learn more about how MUCs work in the digestive system and how they might be linked to elementary canal disorders.